Determination of gender and stature from crown dimensions of primary teeth: An Odontometric study - Basil M. Mathew; Sowndarya Gunasekaran (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Background: Crown dimensions of teeth have been positively correlated with stature and gender. These odontometric values can aid significantly in the forensic identification of individuals in case of mass disasters as teeth are the least affected structures during such calamities. There is a dearth of studies investigating crown dimensions as a tool in forensic identification, especially in the pediatric population. Aim: The aim of the study was to assess the correlation between stature, gender, and crown dimensions (occlusogingival [OG] height and mesiodistal [MD] width) in a pediatric population and to derive mathematical equations to predict stature and gender using these crown dimensions. Materials and Methods: A cross-sectional study was conducted among 1057 South Indian children in the age group of 3–6 years. Impressions of the maxillary dentition were made, and casts were obtained. A Vernier caliper was used to measure the OG height and MD width of teeth 51, 52, 53, 61, 62, and 63. A measuring tape was used to measure the stature of the children, and the gender was noted. These data were subjected to statistical analysis to obtain the results. Results: Male children had a significantly higher mean MD width and OG height with respect to teeth 52, 53, and 62. A statistically significant positive correlation was seen in teeth 62 between stature and crown dimensions indicating an increase in stature with an increase in these crown dimensions. Conclusions: A positive correlation was affirmed between the crown dimensions of teeth 52, 53, and 62, stature and gender of the children. Mathematical equations were also successfully derived using these crown dimensions to predict the stature and gender of children.